Mechanical and acoustic properties of alkali treated agricultural waste reinforced sustainable polyurethane composites - KOÇAK, EMİNE DİLARA; YILDIZ, ZEHRA (My University, 2023)
In this research, polyurethane (PU) foam composites were prepared by using various agricultural waste (rice husk, corn silk, artichoke stem) particles. In order to enhance the compatibility and adhesion between the waste particle and PU matrix, alkali treatment was employed. The alkali treated particles were chemically and morphologically characterized by Fourier transform infrared (FTIR) spectroscopy, cellulose determination instrument, and scanning electron microscopy (SEM), respectively. The effects of the alkali treatment on the structural, morphological, mechanical, and acoustic properties of the overall PU foam composites were all examined. Due to the differences in chemical compositions of the agricultural wastes, the alkali treatment affected the acoustic and mechanical properties of the PU foam composites in varying ratios. The PU foam composite reinforced with alkali treated artichoke stem waste particles showed the highest tensile strength value of 265 kPa, whereas the highest sound absorption value of 40.5% as an enhancement on the acoustic properties compared to the blank PU foam composite was recorded in corn silk waste particle loaded sample.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarım Alet ve Makineleri; Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Agricultural Tools and Machines; Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Malzeme Bilimi; MÜHENDİSLİK, MEKANİK; MALZEME BİLİMİ, KOMPOZİTLER; MALZEME BİLİMİ, SERAMİK; POLİMER BİLİMİ; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; MATERIALS SCIENCE; CHEMISTRY; ENGINEERING, MECHANICAL; MATERIALS SCIENCE, COMPOSITES; MATERIALS SCIENCE, CERAMICS; POLYMER SCIENCE; MATERIALS SCIENCE, MULTIDISCIPLINARY; Seramik ve Kompozitler; Fizik Bilimleri; Malzemelerin mekaniği; Makine Mühendisliği; Polimerler ve Plastikler; Malzeme Kimyası; Ceramics and Composites; Physical Sciences; Mechanics of Materials; Mechanical Engineering; Polymers and Plastics; Materials Chemistry; Agricultural waste; alkali treatment; polyurethane; sound absorption; sustainability